Preteklost na dosegu klika - Majerič Bolka, Branislava (Moderna arhivistika, 2024)
In the paper, the authors present the changes in the provision of access to archival material in the 10-year period from the beginning of 2013 to the end of 2023, which are most reflected in the number of applications, methods of ordering material and the number of reproductions of archival material. They also devoted themselves to research on the use of the Virtual Archive Reading Room, both for reviewing inventories of archive material and for ordering only this. They performed an overview of the most sought-after topics and funds by area, where applications with a construction character are leading with great advantage. They point out that, given the needs of the users, it would be first and foremost important that the most used material be protected from material damage through digitization and that, to the greatest extent possible, access to the material be made possible through the VAČ system.
Keywords: access to arhive records; archive records; archive reding room; arhivska čitalnica; arhivsko gradivo; dostop do arhivskega gradiva; Historical Archives of Ljubljana; published sources; uporaba arhivskega gradiva; use of archive records; virtual archive reading room; virtualna arhivska čitalnica; Zgodovinski arhiv Ljubljana